ACCEPTABILITY AND NUTRIENT CONTENT OF INSTANT DRINK MADE FROM YELLOW SWEET POTATO AND RED KIDNEY BEAN AS AN ALTERNATIVE SUPPLEMENTARY DRINK FOR PREGNANT WOMEN WITH CHRONIC ENERGY DEFICIENCY - Chaidir Masyhuri Majiding; Evy Damayanthi; Mira Dewi (Media Gizi Indonesia, 2021)
Providing supplementary food or drink for pregnant women with chronic energy defi ciency (CED) is one form of specifi c interventions to increase the nutritional intake of pregnant women which is quite eff ective. Supplementary drink made from local food are very appropriate to be developed by considering its nutritional and sensory aspects. This study aimed to develop and to analyze instant powder drink made from yellow sweet potato and red kidney bean as an alternative supplementary drink for pregnant women with chronic energy defi ciency (CED). This study used a completely randomized factorial design with two factors and two replications. The ratio between yellow sweet potato and red kidney beans as the fi rst factor and the addition of maltodextrin as the second factor. Results showed that from 6 formulas, formula with ratio 3:1 of yellow sweet potato and red bean also the addition of 5% maltodextrin (F5) was chosen as the best formula. Based on acceptance test results, instant drink was accepted by pregnant women with percentage of acceptance 89.5% of overall sensory characteristics. Nutrient content analysis showed that instant drink contained 423 kcal of energy, 3.75% of water, 1.52% of ash, 14.28% of protein, 9.92% of fat, 70.53% of carbohydrates, 7.27% of dietary fi ber, 14.4 mg of β-carotene, and 74.22% of protein digestibility. This product can be suggested as an alternative supplementary drink for CED pregnant women because it was acceptable by sensory and the nutrient content had fulfi lled nutritional content requirements of supplementary food for CED pregnant women